Do you speak deutsch? Or, the interaction of languages in foreign language classes in a multilingual environment - Ilona Lekhner; Lechner Ilona; Лехнер Ілона; Густі Ілона; Huszti Ilona (Житомирський державний університет імені Івана Франка, 2025)
Abstract. The aim of the study is to present the different forms of language interaction in a multilingual learning environment, specifically through the foreign language teaching practices of the Ferenc Rákóczi II Transcarpathian Hungarian College of Higher Education. In Transcarpathia, a western region of Ukraine, multilingualism and multilingual language use have become part of everyday life due to its geographical location and the changes of power in the 20th century. The linguistic diversity of the area, including the co-existence of Hungarian, Ukrainian, Romanian, Polish, Russian and Roma, provides a particularly fertile ground for the study of translanguaging and linguistic transfer and interference. The empirical basis of the research is based on our own observations of the language use of Hungarian and/or Ukrainian native speakers majoring in English studying German as a second foreign language at the aforementioned higher educational establishment. Our experience confirmed that in language classes in multilingual contexts, phenomena are often observed where students consciously or spontaneously mobilise multiple linguistic resources in the course of communication. Typical cases of translanguaging, for example in the processes of task comprehension, word search or meaning making, not only testify to the linguistic creativity of learners, but also require flexibility in teaching methods. Positive and negative forms of linguistic transfer (e.g. transfer of similar grammatical structures or phonetic interference) are also common and affect learning outcomes. Our study shows that multilingualism presents not only challenges but also opportunities in foreign language teaching. The conscious integration of multilingual backgrounds and the pedagogical recognition of translanguaging can contribute to the development of linguistic competence and the enhancement of foreign language confidence. Our study stresses the importance of considering the local context in educational practice.

Резюме. Метою даного дослідження є аналіз форм мовної взаємодії в умовах багатомовного навчального середовища на прикладі викладання іноземних мов у Закарпатському угорському інституті ім. Ференца Ракоці ІІ. Закарпаття – західний регіон України, для якого характерне мовне розмаїття, зумовленого історичними обставинами та географічним розташуванням. Співіснування угорської, української, румунської, польської, російської та ромської мов створює унікальне підґрунтя для дослідження явищ транслінгвізму, мовного трансферу та інтерференції. Емпіричну базу дослідження становлять спостереження за мовною поведінкою здобувачів вищої освіти освітньої програми 014 Середня освіта (Англійська мова та література) першого (бакалаврського) рівня вищої освіти, які вивчають німецьку як другу іноземну мову. У процесі дослідження виявлено, що в багатомовному контексті студенти у процесі комунікації свідомо або спонтанно активізують різні мовні ресурси. Типові приклади перекладу, зокрема при розумінні завдань, доборі лексики чи створенні висловлювання, свідчать про мовну креативність студентів і потребують гнучкого підходу до процесу викладання. Доведено, що мовний трансфер має як позитивні, так і негативні форми, наприклад, перенесення граматичних структур або фонетична інтерференція є поширеним явищем і суттєво впливають на результати навчання. Наголошено, що багатомовність створює не лише виклики, а й значні можливості для вдосконалення процесу викладання іноземних мов. Свідома інтеграція транслінгвального підходу та урахування місцевого мовленнєвого контексту можуть сприяти розвитку мовної компетентності та впевненості студентів у володінні іноземною мовою.
Ви розмовляєте Deutsch? – Взаємодія мов на заняттях іноземної мови у закладі вищої освіти в багатомовному середовищі
Редколегія: http://polonistyka.zu.edu.ua/about/editorialTeam
Keywords: multilingualism; translanguaging; language transfer; interference; foreign language teaching; translanguaging pedagogy; classroom language use; багатомовність; транслінгвізм; мовний трансфер; інтерференція; викладання іноземних мов; педагогіка транслінгвізму; мововживання студентів у аудиторії